Search Computing Broadening Web Search - Ceri, Stefano; Brambilla, Marco (Information Systems and Applications, incl. Internet/Web, and HCI, 2012)
Search computing, which has evolved from service computing, focuses on building the answers to complex search queries by interacting with a constellation of cooperating search services, using the ranking and joining of results as the dominant factors for service composition. The field is multi-disciplinary in nature and takes advantage of contributions from other research areas such as knowledge representation, human-computer interfaces, psychology, sociology, economics, and legal sciences. This book is the third in the Search Computing series and contains a collection of 16 papers, which in most cases were contributed to several workshops during 2011 organized by members of the Search Computing project in the context of major international conferences: ExploreWeb at ICWE 2011, Very Large Data Search and DBRank at VLDB 2011, DATAVIEW at ECOWS 2011, and OrdRing at ISWC 2011. The papers provide very useful insights on search computing problems and issues. The book has been divided into four parts focussing on: extraction and integration; query and visualization paradigms; exploring linked data; and games, social search and economics.